Magnetic resonance imaging in osteoarthritis of the knee: correlation with radiographic and scintigraphic findings. Issue 1 (January 1991) - McAlindon, T E; Watt, I; McCrae, F; Goddard, P; Dieppe, P A
Abstract : Twelve knees with a range of severity of knee osteoarthritis were assessed by magnetic resonance imaging (MRI) and technetium-99m labelled hydroxymethylene diphosphonate scintigraphy. Five magnetic resonance pulse sequences were evaluated. Proton density (TR = 1000, TE = 26 ms) and STIR (TR = 1500, TI = 100, TE = 30 ms) were chosen for further use. Abnormalities shown by MRI included joint effusions, meniscal disruption, hyaline cartilage thinning, subchondral signal changes, pseudocysts, and heterogeneity of signal from osteophytes. Certain MRI and scintigraphic appearances correlated: (a) 'hyperintense osteophytosis' and ipsilateral 'tramline' scintigraphic uptake, suggesting increased fat content in 'active' osteophytes; (b) subchondral signal change and 'extended' pattern, possibly reflecting inflammation, synovial leak, or fibrovascular repair; (c) patellofemoral joint signal changes and patellar isotope uptake.